Water quality and macroalgal community structure across coastal sites in the Bima Sea, Indonesia - NIKMAN AZMIN; CATUR RETNANINGDYAH; SUHARJONO SUHARJONO; WAHYU WIDORETNO (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Azmin N, Retnaningdyah C, Suharjono, Widoretno W. 2026. Water quality and macroalgal community structure across coastal sites in the Bima Sea, Indonesia. Biodiversitas 27 (6): d270606. https://doi.org/10.13057/biodiv/d270606. Macroalgae are important primary producers in coastal ecosystems and are highly sensitive to changes in environmental conditions. This study aimed to evaluate the physicochemical water quality and macroalgal community structure in aquaculture and non-aquaculture areas at Wane, Rontu, and Tanjung Mas beaches, Bima Regency, West Nusa Tenggara, Indonesia. Community structure was assessed using community indices, the Importance Value Index (IVI), and multivariate analyses. A total of ten macroalgal taxa were identified, with Sargassum sp. exhibiting the highest IVI values across all study sites (59-81), followed by Halimeda micronesica, Ulva lactuca, and Turbinaria sp., which showed intermediate IVI values. Water temperature and pH remained within ranges suitable for supporting marine life, whereas nitrate and orthophosphate concentrations consistently exceeded water quality reference thresholds across all study sites, although no significant differences were detected among locations (p>0.05). The Shannon-Wiener diversity index (H′) ranged from 1.57 to 2.67, with the highest value recorded at the non-aquaculture site in Wane and the lowest at the non-aquaculture site in Tanjung Mas. Multivariate analyses indicated that variation in macroalgal community structure was generally more strongly associated with differences among beaches than with aquaculture and non-aquaculture site categories, although this pattern was most consistently observed at Tanjung Mas Beach. The findings demonstrate that site-specific environmental characteristics play a key role in shaping macroalgal community structure in the Bima Sea. These results highlight the importance of continuous water quality monitoring and location-based coastal management strategies to support macroalgal conservation and the sustainability of tropical coastal ecosystems.